Nutrition and stress: Two important external factors in polymyalgia rheumatica (Annals of Medical Research, 2021)
Aim: Assessing the relationship between Polymyalgia Rheumatica (PMR) and nutrition and stress.Materials and Methods: 24 patients with PMR and 24 patients without PMR (control group) were included in this pilot study. Patients’ demographics, body mass index (BMI), use of tobacco and alcohol and dietary preferences were reviewed. Mean age of patient group was 65 and 59 in the control group. Both groups were composed of males and females. Patients with medication usage which might affect stress levels or appetite or weight loss, with other systemic diseases which might cause weight loss (malignancies, thyroid issues), with rheumatologic or autoimmune diseases other than PMR, and with psychiatric disorders diagnosed by psychiatrists were excluded from the study. A form was developed to assess the dietary habits of the participants in last 3 months. Objective of this form is to determine the consumption of carbohydrates, proteins, fats and processed food intake of the patients. Stress levels of patients were measured using Perceived Stress Scale (PSS).Results: BMI was significantly higher in PMR group when compared to controls (p0.01). Green vegetable daily consumption frequency was significantly higher in control group (p0.01). In terms of grains, PMR group showed a significantly higher consumption of wheat instead of rice (p=0.026). In terms of oil choice, control group showed a significantly higher consumption of olive oil instead of margarine (p=0.039).No significant difference in terms of PSS scores were seen between the groups (p=0.428).Conclusions: Lower BMI, consumption of green vegetables, rice and olive oil are all related with lowering the risk of PMR development and stress presence does not have a direct relationship with PMR risk.